APLIKASI PEMBELAJARAN PENULISAN HURUF KOREA DASAR(HANGEUL) BERBASIS ANDROID - Hadi Wibowo, Grace Hilda Yuanita; Saefurrohman, Saefurrohman (Information Technology and Telematics, 2018)
Abstract–Korean language is one of the most popular languages today. Korean language is famous for Korean songs and dramas that have captured the attention and hearts of people in the world, not to mention Indonesia.People must often hear JARGON from Korean dramas, such as annyeong, aigoo and gamsahamnida that make people courious how to writing and how the writing and the shape of letters.So, author make this thesis with title “Korean Lessons (Hangeul) Learning Application (Hangeul) Based on Android” or VOKONEA. This learning application that based on android / IOS is so loved by all people, because it’s simple to used and comfortable in anywhere and anytime. VOKONEA using SM (String Matching) for the method and collision algorythm, because the fungtion can match the answer (true / false).